PENGATURAN KONTRAK DALAM VALIDITAS MUAMALAT - Mukhtasar Mukhtasar (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2017)
Contracts in Islamic legal and if there is harmony in legal terms is called akad. In the economic activities that apply the rule of law that all are allowed unless there is proof about that. In business practices required no harmonious interrelationship of the rules, the binding law, sanctions, so that business profits are not demanding profits. The all advantage of transactions can be done and declared valid if there is consent and free from coercion between the two sides. Islamic economic system is a system which is built based on the laws that safeguard the principle of property rights and the sanctity of contract, any form of exploitation that led to the deal inappropriate and cause injustice in the business then it is haram. Maqasid ash-shariah can defined as benefit/welfare/ usefulness of what God has revealed to the shariah. Maqasid ash-shariah aims to achieve goodness, usefulness to avoid crime. Maqasid ash- Shariah can be classified into three parts: Daruriah [basic needs] Hajjiyah [secondary needs] Tahsiniah [tertiary needs] In the stock market has been violated maqasid ash-shariah is faith or confidence in the economic practice is the practice of gambling. In a stock market that causes people don’t want to work hard due to the high profits despite frequent large losses, due to fall in share prices. Trading in the stock market is one example of economic practices that don’t conform with maqasid ash-shariah in doing so need to be modified with islamic business model to keep maqasid islami ash-shariah. Keyword : contract, economics, maqasid ash-shariah, market